Civil Liability of Doctors for the Use of Dermal Fillers Without a Marketing Authorization in Medical Aesthetic Services - Cahyarini, Citra; Sutarni, Nanik; Imroatus Sholikah, Dwi; Picaso, Rivan (Law Development Journal, 2026)
The use of dermal fillers in medical aesthetic services is growing rapidly because this procedure is considered to provide fast results, is minimally invasive, and is increasingly popular with the public. Dermal fillers are essentially non-surgical procedures to improve facial contours, reduce wrinkles, or increase soft tissue volume. However, this procedure still carries medical and legal risks and must be performed with safe, legal products that meet the doctor's competence. Legal issues arise when doctors use dermal fillers without a marketing authorization, because this action has the potential to violate medical device safety regulations, cause patient harm, and open up opportunities for civil liability. This study aims to analyze the civil liability of doctors in the use of dermal fillers without a marketing authorization using the Civil Code, consumer protection, and health law approaches. The results of the study indicate that doctors can be held liable based on unlawful acts, breach of contract, and breach of professional obligations and the obligation to ensure the legality of the products used. From a consumer protection perspective, patients are considered consumers of health services who have the right to security, correct information, and compensation for any losses incurred. The use of dermal fillers without a marketing authorization is not only an administrative violation but can also result in serious civil liability for doctors.